Hepatorenal Polycystosis Complicated By Hepatic Cirrhosis: A Case Report - Aouroud, Meryem; Jarti, Mariama; Haida, Marj Zohour; Jallouli, Abderahmane; Ait Errami, Adil; Oubaha, Sofia; Samlani, Zouhour; Krati, Khadija (International Journal of Innovative Research in Medical Science, 2021)
Polycystic liver disease is most commonly associated with autosomal dominant polycystic kidney disease. Hepatic cysts are the most common extrarenal manifestation of autosomal dominant polycystic kidney disease. The progression to cirrhosis remains rare, and the data is sparse, the only curative treatment is liver transplantation. We report the case of a young patient with hepato-renal polycystosis at the stage of cirrhosis.